Project Based Learning Methodologies Applied to Large Groups of Students: Airplane Design in a Concurrent Engineering Context. Issue 29 (2015) - Esteban, Sergio; Arahal, Manuel Ruiz
Abstract: This article presents a college course experience taught in the final academic year of the Aerospace Engineering program at the University of Seville, in which students design an airplane taking the specification submitted by the instructor, following the Project Based Learnig (PBL) methodology. Students are organized into groups forming "companies" that have to defend their proposed design with the "client". The article presents the usual steps of the PBL methodology showing the feasibility of applying this methodology to large workgroups. The complete design of an aircraft is the result of a compromise between knowledge, experience and teamwork in a collaborative environment. The students need to understand that each of the different areas are necessary pieces of the larger puzzle of aircraft design, and they need to find the key that solves this puzzle. The main objective of this course it to provide instructions to complete that puzzle by introducing concurrent engineering and PBL methodologies.